PERANCANGAN BUKU REFERENSI PEMBUATAN TENUN IKAT TRADISIONAL BAGI KALANGAN REMAJA DI KABUAPTEN SIKKA KEPULAUAN FLORES SEBAGAI BENTUK PELSETARIAN BUDAYA LOKAL - Lanu, Vero; Dewanto, Thomas Hanandry; Karsam, Karsam (Jurnal Art Nouveau, 2016)
The existence of weaving in the life of society have a role and a very valuable both economically, socially and culturally. These values can be seen from the behavior or habits of local communities Flores. Cultural importance of weaving makes the writer tries to design reference books related to the process of making traditional ikat in Sikka Regency society, especially on the island of Palue which is one of the islands in East Nusa Tenggara (NTT). The book is designed specifically reserved for teenagers in Sikka district, because the author assumes that the youth in the district slow sea change will be the development of increasingly sophisticated technology, resulting in lack of interest of youth to preserve back traditional culture, one that is with weaving.Keyword : buku refrensi, tenun ikat, flores, tradisi